Pengaruh Kompetensi terhadap Kinerja Perangkat Nagari dalam Pengelolaan Keuangan Nagari di Kabupaten Tanah Datar - Tania Rozanti (Journal of Education on Social Science (JESS), 2017)
This study aimed to determine the influence of competence on performance of nagari government apparatus in managing nagari finance in Tanah Datar regency. This study was conducted with quantitative approach. The population of this study was all nagari government apparatus in Tanah Datar regency as many as 525 people consisting of nagari secretary, nagari treasurer, and five head of nagari affairs. The sample in this study consisted of 227 respondents determined with Slovin formula and Multi Stage Random Sampling technique. The data of this study were collected through questionnaire with likert scale measurement. Data of this study were analyzed with multiple linear regression test. The finding of this study indicated that the influence of knowledge sub-variables on the performance of nagari government apparatus in nagari financial management was 5.6%; the influence of skill on the financial management was equal to 7,3%; and the influence of attitude sub variable on the nagari financial management was equal to 8,5%. At the same time, the influence of knowledge, skills, and attitudes on the performance of financial management was 10.3%. Thus it could be concluded that the competence of nagari government apparatus consisting of knowledge, skills, and attitudes significantly influenced their performance in nagari financial management.